2017
DOI: 10.1371/journal.pone.0172538
|View full text |Cite
|
Sign up to set email alerts
|

Acetylcholine versus cold pressor testing for evaluation of coronary endothelial function

Abstract: BackgroundAssessment of coronary endothelial function with intracoronary acetylcholine (IC-Ach) provides diagnostic and prognostic data in patients with suspected coronary microvascular dysfunction (CMD), but is often not feasible due in part to the time and expertise needed for pharmacologic mixing. Cold pressor testing (CPT) is a simple and safe stimulus useful for either invasive or non-invasive endothelial function testing and myocardial perfusion imaging but has not been specifically evaluated among sympt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
(33 reference statements)
0
8
0
Order By: Relevance
“…We and others have demonstrated that the endothelial reactivity in response to these pharmacologic probes indicative of vasomotion during physiologic stimulation as well. Coronary flow and epicardial responses to pacing, cold pressor testing and mental stress correlate with the responses to acetylcholine 7,[15][16][17] . We also have shown that forearm microvascular dilation in response to exercise mediated by NO release is greater in healthy subjects compared to those with hypercholesterolemia 18 .…”
Section: Introductionmentioning
confidence: 98%
“…We and others have demonstrated that the endothelial reactivity in response to these pharmacologic probes indicative of vasomotion during physiologic stimulation as well. Coronary flow and epicardial responses to pacing, cold pressor testing and mental stress correlate with the responses to acetylcholine 7,[15][16][17] . We also have shown that forearm microvascular dilation in response to exercise mediated by NO release is greater in healthy subjects compared to those with hypercholesterolemia 18 .…”
Section: Introductionmentioning
confidence: 98%
“…This method involves wrapping an ice pack around the forearm or placing it on the patient's forehead for two minutes with angiography then repeated. This works via the pathway of sympathetic (and likely also parasympathetic neuro humoral responses) stimulation though this it is postulated that it may be more complex than this as direct trials comparing this technique with intracoronary acetylcholine have demonstrated a greater effect on coronary vessel change with CPT (96,97). In a normal coronary circulation, sympathetic activation provokes endothelium dependent vasodilation.…”
Section: Methodologies For the Assessment Of Endothelial Functionmentioning
confidence: 99%
“…Non-invasive methods that assess coronary spams are available, for example the implementation of mental stress, hyperventilation or the cold-pressor technique to provoke spasm. However, besides the lack of experience in most centres, there is little data about the validity and safety of these methods [ 30 ].…”
Section: Non-invasive Alternatives To Diagnose Coronary Vascular Dysfmentioning
confidence: 99%